2015
DOI: 10.1021/acs.chemmater.5b00957
|View full text |Cite
|
Sign up to set email alerts
|

The Intercalation Phase Diagram of Mg in V2O5 from First-Principles

Abstract: We have investigated Mg intercalation into orthorhombic V 2 O 5 , one of only three cathodes known to reversibly intercalate Mg ions. By calculating the ground-state Mg x V 2 O 5 configurations and by developing a cluster expansion for the configurational disorder in δ-V 2 O 5 , a full temperature− composition phase diagram is derived. Our calculations indicate an equilibrium phase-separating behavior between fully demagnesiated α-V 2 O 5 and fully magnesiated δ-V 2 O 5 , but also motivate the existence of pot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
178
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(202 citation statements)
references
References 73 publications
(132 reference statements)
12
178
5
Order By: Relevance
“…In addition to unveiling complicated mechanism in the magnesiation of rMB cathode (Gautam et al, 2015Ling et al, 2015), computational work helps find suitable cathode candidate for experimental studies. Liu et al (2015) found that among various spinel compounds MnO2 is particularly interesting due to the stability especially at charged state.…”
Section: Computational Studiesmentioning
confidence: 99%
“…In addition to unveiling complicated mechanism in the magnesiation of rMB cathode (Gautam et al, 2015Ling et al, 2015), computational work helps find suitable cathode candidate for experimental studies. Liu et al (2015) found that among various spinel compounds MnO2 is particularly interesting due to the stability especially at charged state.…”
Section: Computational Studiesmentioning
confidence: 99%
“…• Li in spinel LiTiS 2 (linear MEP); 51,52 • Zn in spinel ZnMn 2 O 4 (linear MEP); 23,53 • Zn in post-spinel ZnMn 2 O 4 (linear MEP); 54 • Li in olivine LiFePO 4 (curved MEP); [55][56][57][58][59] • Mg in δ-MgV 2 O 5 (curved MEP); 25,26,60,61 • Ca in layered CaMoO 3 (curved MEP). 62 To quantify the accuracy of the PathFinder algorithm in reproducing the geometry of the fully converged MEP, we define an error metric, shown schematically in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…b) Author to whom correspondence should be addressed. Electronic mail: gceder@berkeley.edu community and specifically in battery research, NEB has been applied successfully to address Li [17][18][19][20][21][22] and multivalent ion [23][24][25][26]66,67 diffusion in a multitude of cathode materials and ionic conductors. 27,28 In a NEB calculation, a group of images (replicas) of the system is interpolated between the initial and final states.…”
Section: Introductionmentioning
confidence: 99%
“…Other first principles calculations on V 2 O 5 highly overestimated the c-lattice parameters, and hence produced large discrepancies in physical properties 41, 51-53, 72, 74-79,17, 65 . Recent studies [80][81][82][83][84][85][86] (TABLE I). Moreover, the calculated V-O bond lengths and bond angles by this approach agree very well with the experimental values.…”
Section: B Role Of Van-der Walls and Hubbard Onsite Interaction Inv mentioning
confidence: 99%